FUZIL POET OF UZBEK FOLK ORAL CREATIVITY - Boykhurozov Diyorbek Sherzod ögli (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Shaykhzoda not only wrote works in all types and genres of artistic creation, but also effectively created as a literary critic and critic. Shaikhzoda was a versatile talent. In addition to poems and epics, he also created dramas with a very high artistic capacity. Shaykhzoda began writing later in his life.